Addition flame‐retardant effect of nonreactive phosphonate and expandable graphite in rigid polyurethane foams. Issue 10 (12th November 2017) - Li, Linjie; Chen, Yajun; Qian, Lijun; Xu, Bo; Xi, Wang
ABSTRACT: A series of flame‐retardant rigid polyurethane foams (RPUFs) containing nonreactive phosphonate (5‐ethyl‐2‐methyl‐1, 3, 2‐dioxaphosphorinan‐5‐yl) methyl dimethyl phosphonate P‐oxide (EMD) and expandable graphite (EG) were prepared by water blown. The flame‐retardant properties and mechanism of EMD/EG on RPUFs were systematically investigated. The EMD/EG system effectively increased the limiting oxygen index (LOI) value and decreased the values of total heat release (THR), av‐effective heat of combustion (EHC), pk‐heat release rate (HRR), total smoke release (TSR) of RPUFs. The impact values of LOI, THR, and av‐EHC resulted by EMD/EG system are nearly equal to the sum of the impact values by EMD and EG individually in RPUFs, which implies the addition flame‐retardant effect from EMD and EG. EMD alone exerted excellent gas‐phase flame‐retardant effect by releasing PO fragments with quenching effect. The firm residue produced by EMD combined well with the loose and worm‐like expanded graphite from EG further to form compact and expanded char layer, which brought excellent barrier effect and filtration effect to matrix. That's why pk‐HRR and TSR values of RPUF reduced. Depending on the simultaneous actions of EMD/EG system in gas phase and condensed phase during combustion, the flame‐retardant effects from nonreactive phosphonate and EG on RPUFs were added together. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45960. Abstract :